Computerised Car Workshop System / Sivanesen Vaitilinggam - Sivanesen, Vaitilinggam (2003)
Today's car workshop centres are sophisticated businesses and their popularity is ever growing as the modern society. One of the premier car workshops in Penang is the Impian workshop, which currently has about 400 customers and provides a wide range of services. The workshop was started, 5 years ago. Today. the workshop is very popular among Penangites. Since it first started, the business in workshop grew rapidly every year. This i due to the hard work of owner and his good management skills and also good customer service provided by the employees. The organisation structure of the car workshop is mainly divided into the clerks and other lower level staffs (mechanics).